Internalizing and externalizing factors on the pathway from adverse experiences in childhood to non-medical prescription opioid use in adulthood. (1st April 2019) - Quinn, Kelly; Frueh, Bartley C.; Scheidell, Joy; Schatz, Daniel; Scanlon, Faith; Khan, Maria R.
Highlights: Every ACE increase is associated with 32/27% higher odds of NMPO for males/females. Internalizing and externalizing factors partially explain the ACE to NMPO pathway. Delinquency is a strong mediator for males and females. Abstract: Background: Research demonstrates strong associations between adverse childhood experiences (ACEs) and non-medical prescription opioid use (NMPO), but pathways are not understood, hindering prevention and treatment responses. Methods: We assessed hypothesized mediators of the association between ACEs and NMPO in a nationally-representative U.S. sample. National Longitudinal Study of Adolescent to Adult Health data (N = 12, 288) yielded an ordinal exposure comprising nine ACEs (neglect; emotional, physical, sexual abuse; parental incarceration and binge drinking; witnessed, threatened with, experienced violence) and a binary lifetime NMPO outcome. Nine potential mediators measured in adolescence and/or adulthood included depression, anxiety, suicidality, delinquency, impulsivity, and risk-taking. We estimated adjusted odds ratios (AOR) and 95% confidence intervals (CI) for sex-stratified associations of: ACEs and mediators; mediators and NMPO; and ACEs and NMPO adjusting for mediators individually and simultaneously. Results: All associations of ACEs and mediators were statistically significant and similar by sex. All mediators had statistically significant associations with NMPO (except one depression measurement for each sex). Delinquency was strongly associated with ACEs and NMPO and was the strongest individual mediator. Every ACE increase was associated with increased NMPO odds of 32% for males and 27% for females. Adjusting for all mediators, odds of NMPO were attenuated partially for males [AOR = 1.18 (95% CI:1.07, 1.31)] and somewhat more for females [AOR = 1.11 (95% CI:1.00, 1.25)]. Conclusions: Internalizing and externalizing factors partially explained the pathway from ACEs to NMPO. Substance abuse may be more difficult to treat with co-occurring psychopathologies and maladaptive behaviors, highlighting the need to address trauma early in life.